Cranial aspergilloma masquerading as meningioma. (9th January 2013) - Verma, Ritu; Singh, Prabhat; Kumar, Achal; Paliwal, Vimal Kumar
Abstract : Cranial aspergillosis may present as meningitis, cerebral abscess, cerebral infarcts/haemorrhages or extra-axial mass. Extra-axial cranial aspergilloma may mimic meningioma owing to mass-like characteristics and intense contrast enhancement on MRI there by delaying the diagnosis and further worsening the already bad prognosis in these patients. We present a 45-year-old gentleman who presented with signs of raised intracranial hypertension, secondary optic atrophy and a contrast-enhancing mass arising from the planum sphenoidale. Postoperatively, mass was diagnosed as aspergilloma on histopathology and culture. Despite antifungal treatment, patient could not be saved due to large artery infarcts in the immediate postoperative period. We discuss the clinical and MRI features that could help to have sufficient and early suspicion of fungal aetiology in these patients.